Sengketa Kewenangan Lembaga Negara - Febiana, Fina (Peneliti.net, 2024)
Resolving disputes about the jurisdiction of governmental entities assigned powers under the 1945 Constitution is an ongoing responsibility of the Constitutional Court. Even in constitutional law, the phrase